Development of a dynamic incentive and penalty program for improving the energy performance of existing buildings - Koo, Choongwan; Hong, Taehoon (Technological and Economic Development of Economy, 2018)
The positive effectiveness of energy policy instruments such as national carbon emissions reduction target (CERT) and energy performance certificates can be achieved by encouraging the voluntary participation of the public in the energy-saving campaign. Towards this end, this study aimed to develop a dynamic incentive and penalty program for improving the energy performance of existing buildings. Four types of incentive programs and four types of penalty programs were established based on three comparison criteria. As a building-level, the first comparison criterion is the averaging approach based on similar cases that can be retrieved using a simplified case-based reasoning model. As a community-level, the second comparison criterion is one-step higher operational and letter rating than the grade of a given building. As a national-level, the third comparison criterion is the operational and letter rating as the minimum criteria for achieving the national CERT. In this study, an elementary school facility located in Seoul, South Korea was selected to validate the applicability of the developed program. As a result, besides the category benchmark, the various comparison criteria should be provided to the public to encourage the voluntary participation of the public in the energy-saving campaign. First published online: 19 Feb 2017